Association of mold exposure and solid household fuel use with depression and anxiety among older adults in China - Xinyan Ma; Hanqing Zhao; Yan Wang; Mengdi Hou; Wei Liu; Minghui Sun (Environmental Health)
Abstract Background Exposure to mold and solid cooking fuels represents a significant environmental health concern, contributing substantially to indoor air pollution among elderly populations. However, the association between mold exposure, household fuel use, and mental health remains poorly understood. Here we examine individual and joint associations of these exposures on depression, anxiety, and their co-occurrence in older adults. Methods We evaluated 9,243 elderly participants from the eighth survey wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) to explore the associations between mold exposure, solid fuel use, and depression, anxiety, and their co-occurrence. Multivariable logistic regression models were employed to quantify these relationships, with adjusted odds ratios (aOR) and 95% confidence intervals (CI) reported. Results The study identified a depression prevalence of 13.61% and an anxiety prevalence of 11.79%. Participants exposed to mold demonstrated significantly higher odds of depression (OR = 2.26, 95% CI = 1.93–2.63), anxiety (OR = 2.11, 95% CI = 1.80–2.48), and their co-occurrence (OR = 2.58, 95% CI = 2.10–3.16), compared to participants without mold exposure. Moreover, the use of solid fuels for cooking, as opposed to clean fuels, was correlated with higher occurrence of depression (OR = 1.27, 95% CI = 1.10–1.47), anxiety (OR = 1.31, 95% CI = 1.12–1.52), and their co-occurrence (OR = 1.36, 95% CI = 1.10–1.67). Notably, solid fuel use appeared to attenuate the association between mold exposure and anxiety (Relative excess risk due to interaction [RERI] = -0.22, 95% CI = -0.44, -0.01). Conclusions The study found that exposure to mold and use of solid fuels may be associated with higher prevalence of depression, anxiety, and their co-occurrence. Further prospective studies are warranted to validate our findings.